Sphere of Claim’s Application and Condition of Requirement’s Satisfaction about Recognition of the Right or Encumbrance by Absent - I. V. Popov (Сибирское юридическое обозрение)
The key factor in choosing a proprietary method of protecting civil rights is the question of ownership of an item. In a situation when the land plot is transferred under a deal to a new owner, who subsequently made a deal to alienate him to a third party, the original owner cannot be recognized as a person who has retained possession, despite the fact that access to the land plot is free, did not begin to use it, did not enclose and did not take other measures to visualize their possession. In this case, the claim for recognition of the right absent is not applicable. Protection of rights should be carried out with the help of a vindication suit. The Author, fearing the expansion of the scope of the claim for recognizing the right absent, which is not covered by the limitation period, gives arguments that restrict the application of this claim strictly to the cases listed in par. 4 p. 52 of the Resolution of the Plenum No. 10/22, when: the ownership of the same property is registered for different persons; the title to movable property is registered as real estate; mortgage or other encumbrance ceased.